Transmission Structured Illumination Microscopy for Quantitative Phase and Scattering Imaging - Wen, Kai; Ma, Ying; Liu, Min; Li, Jianlang; Zalevsky, Zeev; Zheng, Juanjuan (Frontiers in Physics, 2021)
In this paper, we demonstrate a digital micromirror device (DMD) based optical microscopic apparatus for quantitative differential phase contrast (qDIC) imaging, coherent structured illumination microscopy (SIM), and dual-modality (scattering/fluorescent) imaging. For both the qDIC imaging and the coherent SIM, two sets of fringe patterns with orthogonal orientations and five phase-shifts for each orientation, are generated by a DMD and projected on a sample. A CCD camera records the generated images in a defocusing manner for qDIC and an in-focus manner for coherent SIM. Both quantitative phase images and super-resolved scattering/fluorescence images can be reconstructed from the recorded intensity images. Moreover, fluorescent imaging modality is integrated, providing specific biochemical structures of the sample once using fluorescent labeling. We believe such a simple and versatile apparatus will find wide applications in biomedical fields or life science.